THE USE OF CODE MIXING IN SUMITOMO COMPANY: SOCIOLINGUISTICS APPROACH - Nila Sari Haloho; Mhd. Johan Johan (Asosiasi Ide Bahasa Kepri, 2022)
The goal of this study was to discover the different code mixing types and the reasons why the leader spoke code mixing during in the meeting with employees. On Monday, he presided over the meeting, which included some code mixing. In this research, the writer used a qualitative descriptive method. The data were taken by recording the utterance of the leader then observed the words that referred to code mixing and the reason of choosing to use code mixing. They are found three types of code mixing the first intra-sentential code mixing, the second intra- lexical form and the last is the pronunciation changing.